Therapeutic outcomes of transplantation of amniotic fluid-derived stem cells in experimental ischemic stroke - Tajiri, Naoki; Acosta, Sandra; Portillo-Gonzales, Gabriel S.; Aguirre, Daniela; Reyes, Stephanny; Lozano, Diego; Pabon, Mibel; Dela Peña, Ike; Ji, Xunming; Yasuhara, Takao; Date, Isao; Solomita, Marianna A.; et al. (Frontiers in Cellular Neuroscience, 2014)
Accumulating preclinical evidence suggests the use of amnion as a source of stem cells for investigations of basic science concepts related to developmental cell biology, but also for stem cells’ therapeutic applications in treating human disorders. We previously reported isolation of viable rat amniotic fluid-derived stem (AFS) cells. Subsequently, we recently reported the therapeutic benefits of intravenous transplantation of AFS cells in a rodent model of ischemic stroke. Parallel lines of investiagtions have provided safety and efficacy of stem cell therapy for treating stroke and other neurological disorders. This review article highlights characterization of AFS cells’ phenotype and their transplant-mediated functional effects, the need for investigations of mechanisms underlying AFS cells’ therapeutic benefits and discusses lab-to-clinic translational gating items in an effort to optimize the clinical application of cell transplantation for stroke.